Effect of Curcumin in Feed for Treating Striped Catfish (Pangasiodon hypopthalmus) Infected Bacteria Aeromonas hydrophila - Poltak Pakpahan; Syawal, Henni; Riauwaty, Morina (Faculty of Fisheries and Marine, Universitas Riau, 2020)
Curcumin is one of the secondary metabolite compounds products that can increase the immune system of fish against bacterial attack. The purpose of this research was to find out the changes in the erythrocytes of a striped fish that were infectious bacteria A. hydrophila and treated with feeding containing curcumin and know the best dose of curcumin extract in the feed. This research was conducted in September to November 2019. The test fish used was the seed of a striped fish that measures 8-10 cm by 150 tails. Method used was the method of experimental and complete random design a factor of 5 levels of treatment and 3 times repeated, the treatment was Kn (feeding without the extract of curcumin and not infected with bacteria A. hydrophila), Kp (feeding without being given curcumin extract and infectious bacteria (A. hydrophila), P1 (addition of curcumin in feed at a dose of 0.7 g/kg), P2 (0.9 g/kg), P3 (of 1.1g/kg). The results shown that P3 treatment was the best treatment with a < 0.05 P where in a total of erythrocytes was 2.46 x 106 cells/mm3. Hemoglobin 9.4 g/dl, hematocrit value of 32.3%, and survival rate was 90%. Curcumin was able to treat fish from an A. hydrophila infection